1997
DOI: 10.1016/s0006-3495(97)78707-1
|View full text |Cite
|
Sign up to set email alerts
|

Activation-Dependent Subconductance Levels in the drk1 K Channel Suggest a Subunit Basis for Ion Permeation and Gating

Abstract: Ion permeation and channel opening are two fundamental properties of ion channels, the molecular bases of which are poorly understood. Channels can exist in two permeability states, open and closed. The relative amount of time a channel spends in the open conformation depends on the state of activation. In voltage-gated ion channels, activation involves movement of a charged voltage sensor, which is required for channel opening. Single-channel recordings of drk1 K channels expressed in Xenopus oocytes suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
126
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(139 citation statements)
references
References 61 publications
12
126
0
1
Order By: Relevance
“…A channel can be seen to dwell in multiple levels for prolonged periods during its initial activation (Fig. 4A), with sublevels visited briefly and interspersed by rapid switching between open and closed levels, as previously seen in Kv channels (11). The mean time to reach the main amplitude (level 4) from the start of each sublevel opening burst was 209 ± 46 ms (n = 21 bursts), excluding two bursts where the channel opened to levels >4 for brief periods and then closed for ∼750 and 1,460 ms, respectively, before reopening and subsequently attaining the main conductance level.…”
Section: Resultssupporting
confidence: 59%
See 3 more Smart Citations
“…A channel can be seen to dwell in multiple levels for prolonged periods during its initial activation (Fig. 4A), with sublevels visited briefly and interspersed by rapid switching between open and closed levels, as previously seen in Kv channels (11). The mean time to reach the main amplitude (level 4) from the start of each sublevel opening burst was 209 ± 46 ms (n = 21 bursts), excluding two bursts where the channel opened to levels >4 for brief periods and then closed for ∼750 and 1,460 ms, respectively, before reopening and subsequently attaining the main conductance level.…”
Section: Resultssupporting
confidence: 59%
“…The highest prevalence of sublevels was observed at voltages expected to activate one set of subunits but not the other, and so it was concluded that subconductance levels arise from heteromeric pore conformations. Such a mechanism for subconductance is consistent with the observation of sublevels coupled to activation in the Shaker (10, 18) and K v 2.1 channel (11,17). Therefore, the presence of sublevels in I Ks may have important implications for the gating of this channel complex.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…Channels can also open partially, leading to a subconductance state that has a smaller current (27,64,104). In contrast to other ion channels (66), the gating behavior of this subconductance state was found to be similar to the main conductance state (64).…”
Section: J Single-channel Recordingsmentioning
confidence: 99%